2009
DOI: 10.1021/ac901172a
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Samples Stored as Individual Plugs in a Capillary by Electrospray Ionization Mass Spectrometry

Abstract: Droplets or plugs within multiphase microfluidic systems have rapidly gained interest as a way to manipulate samples and chemical reactions on the femtoliter to microliter scale. Chemical analysis of the plugs remains a challenge. We have discovered that nanoliter plugs of sample separated by air or oil can be analyzed by electrospray ionization mass spectrometry when pumped directly into a fused silica nanospray emitter tip. Using leu-enkephalin in methanol and 1% acetic acid in water (50:50 v:v) as a model s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 32 publications
(64 reference statements)
2
84
1
1
Order By: Relevance
“…This concentration range was tested based on the amount of choline formed during the enzyme assay. (Our previous work has suggested that lower concentrations can be used for assays that require it as the segmented flow electrospray method has high sensitivity [17].) As shown in Figure 4b, choline signal increased with its concentration nonlinearly while chlormequat signal decreased with increasing choline concentration.…”
Section: Quantificationmentioning
confidence: 92%
See 2 more Smart Citations
“…This concentration range was tested based on the amount of choline formed during the enzyme assay. (Our previous work has suggested that lower concentrations can be used for assays that require it as the segmented flow electrospray method has high sensitivity [17].) As shown in Figure 4b, choline signal increased with its concentration nonlinearly while chlormequat signal decreased with increasing choline concentration.…”
Section: Quantificationmentioning
confidence: 92%
“…Air-segmented sample plugs were generated using the system illustrated in Figure 1, similar to that recently described [17]. To fill the tube with air-segmented samples, a computer-controlled xyzmicropositioner (built in-house from XSlide assemblies; Velmex Inc., Bloomfield, NY, USA) was used to move the inlet of the Teflon tubing from sample-to-sample on the multiwell plate while the pump was operated at a fixed aspiration rate.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years droplet microfluidics has gained interest for (bio-)chemical reactions [12][13][14][15] and for single cell studies 16,17 . Additionally, this technique was applied for introducing samples in electrospray ionization mass spectrometry 18,19 and for preparing samples in matrix-assisted laser desorption/ionization mass spectrometry 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…ESI-MS analysis of aqueous droplets has been achieved by directly coupling a segmented flow system with MS (Pei et al, 2009), but this method has some potential risks including instability of the electrospray due to oil accumulation at the tip, introduction of chemical background, and contamination of the MS instrument. Hence, it is generally necessary to extract the aqueous droplet from the oil phase for further separation or MS analysis.…”
Section: Introductionmentioning
confidence: 99%